Will Latin America join petroleum’s new world order? - Pugliaresi, L (Oxford Institute for Energy Studies, 2015)
The surge in crude oil and natural gas liquids production from the USA and Canada, totalling over 6 million barrels/ day (mb/d) since 2006–7 (see graph on right), is a remarkable achievement of technological innovation and risk taking. This liquids growth arrived on the heels of large-scale and low-cost development of natural gas supplies from so-called tight or unconventional formations. US production growth has been driven by long-term improvements in the application of both the art and science of horizontal drilling and hydraulic fracturing. In the years just prior to the emergence of the US petroleum renaissance, Canada achieved substantial improvements in both mining and steam-assisted gravity drainage (SAGD) extraction techniques from the McMurray Formation in the Western Canada Sedimentary Basin. These North American (sans Mexico) unconventional petroleum developments are altering flows in world crude oil trade, shifting long-term price expectations, and challenging long-held conventional wisdom on US energy policy promulgated in an era of scarcity.